AODWE-004 Maintenance of quality of life improvement in a phase 3 study of tofacitinib for patients with moderately to severely active ulcerative colitis. (17th June 2017) - Panés, J; Rubin, DT; Vermeire, S; Lindsay, JO; Sands, BE; Su, C; Friedman, G; Zhang, H; Kayhan, C; Manuchehri, A; Healey, P
Abstract : Introduction: Tofacitinib is an oral, small molecule Janus kinase inhibitor that is being investigated for ulcerative colitis (UC). Tofacitinib 10 mg twice daily (BID) improved quality of life (QoL) in the Phase 3 OCTAVE Induction 1 and 2 studies of patients (pts) with moderate to severe UC. 1 Method: OCTAVE Sustain (NCT01458574 ) was a Phase 3, 52 week, randomised, double-blind, placebo (Pbo)-controlled study in pts completing OCTAVE Induction 1 or 2 with clinical response (≥3 points and ≥30% decrease from baseline (BL) Mayo score plus decrease in rectal bleeding subscore (RBSS) of ≥1 or RBSS ≤1). Pts were re-randomised (1:1:1) to Pbo, tofacitinib 5 or 10 mg BID. QoL was assessed at Weeks 24 and 52 using the 32-item Inflammatory Bowel Disease Questionnaire (IBDQ) and the Short Form-36 (SF-36v2, 1 week recall; 8 domain scores and Physical/Mental Component Summaries [PCS and MCS]). Clinically relevant endpoints including IBDQ Remission (IBDQ Score ≥170) and Response (≥16 point improvement from induction BL IBDQ Score) were compared by Cochran-Mantel-Haenszel chi-square test. Continuous endpoints were analysed using a linear mixed-effects model. Results: OCTAVE Sustain randomised 593pts (Pbo: n=198; 5 mg BID: n=198; 10 mg BID: n=197). At Sustain BL, mean IBDQ total score ranged from 166.7–167.7, and mean SF-36 PCS and MCS ranged from 49.3–50.5 and 47.8–49.0, respectively, across groups. There was minimal change from BL at Week 24 and 52 in the total IBDQ scores in the tofacitinib groups, while there was a worsening (decrease) in the Pbo group. Both the tofacitinib 5 and 10 mg BID groups showed significant difference in change from Sustain BL in total IBDQ scores at Weeks 24 and 52 compared to Pbo (all p<0.001) (Table). Significantly more patients achieved IBDQ remission and response with both tofacitinib doses vs Pbo at all time points (all p<0.001) (Table). Mean changes from Sustain BL in SF-36 PCS and MCS and all individual domain scores showed similar benefit with both tofacitinib doses vs Pbo at Weeks 24 and 52 (all p<0.001) (Table). Conclusion: For pts with moderate to severe UC and clinical response to induction therapy, significant and clinically meaningful improvements in QoL (IBDQ; SF-36) were maintained with tofacitinib 5 and 10 mg BID vs Pbo through 52 weeks maintenance therapy. References: . Panés J, et al. J Crohns Colitis2016; 10: S283. Disclosure of Interest: J Panés Conflict with: AbbVie and MSD, Conflict with: AbbVie, Boehringer Ingelheim, Genentech-Roche, Janssen, Pfizer Inc, Takeda, and TiGenix, Conflict with: AbbVie, Janssen, MSD, and Pfizer Inc, D Rubin Conflict with: AbbVie, Genentech, Janssen, Takeda, and UCB, Conflict with: AbbVie, Amgen, Janssen, Pfizer Inc, Takeda, and UCB, S Vermeire Conflict with: Centocor, AbbVie, Takeda and Merck, Conflict with: Takeda, Roche/Genentech, Merck, Centocor, AbbVie, UCB, Pfizer, Ferring, Second Genome and Galapagos, Conflict with: Merck, AbbVie, Takeda, Pfizer, Ferring, Falk and Centocor, J Lindsay Conflict with: MSD, Hospira (Pfizer Inc), Shire and Takeda, Conflict with: AbbVie, Celgene, Ferring, Janssen, Merck, Robarts Clinical Trials, Shire, Pfizer Inc and Takeda, Conflict with: AbbVie, Allergan, Ferring, Janssen, MSD, Shire and Takeda, Conflict with: Advisory Board: AbbVie, Atlantic Healthcare, Ferring, Hospira, Janssen, MSD, NAP, Shire, Pfizer, Takeda and Vifor, B Sands Conflict with: AbbVie, Celgene, GlaxoSmithKline, Janssen R and D, Pfizer Inc, Prometheus Laboratories and Takeda, Conflict with: AbbVie, Akros Pharma, Amgen, AstraZeneca, Boehringer Ingelheim, Celgene, Forest Research Institute, Lilly, MedImmune, Puretech Ventures, LLC, Receptos, Salix, Shire, Takeda, Topivert Pharma, Vedanta Biosciences, Bristol-Myers Squibb, Janssen R and D, Luitpold Pharmaceuticals, Pfizer Inc, Prometheus Laboratories, Synergy Pharmaceuticals, Takeda, Theravance Biopharma and Tigenix, C Su Conflict with: Pfizer Inc, Conflict with: Pfizer Inc, G Friedman Conflict with: Pfizer Inc, Conflict with: Pfizer Inc, H Zhang Conflict with: Pfizer Inc, Conflict with: Pfizer Inc, C Kayhan Conflict with: Pfizer Inc, Conflict with: Pfizer Inc, A Manuchehri Conflict with: Pfizer Inc, Conflict with: Pfizer Ltd, P Healey Conflict with: Pfizer Inc, Conflict with: Pfizer Inc